AB0950 Minimal disease activity in real life in psoriatic arthritis. (12th June 2018) - Ureyen, S.B.; Solmaz, D.; Al Asoimi, N.; ,; Dalkilic, E.; Can, M.; Erden, A.; Ozisler, C.; Cinar, M.; Kilic, L.; Kalyoncu, U.; Aydin, S.Z.; et al.
Abstract : Background: Minimal disease activity ( MDA) is an important target in patients with psoriatic arthritis (PsA), however it is also criticised for having low threshold for patient reported outcomes (PRO). Objectives: The aim of the study was to assess the prevalence of MDA components in patients with PsA and to evaluate disease characteristics and patterns in patients with or without MDA. Methods: PsArt-ID (Psoriatic Arthritis- International Database) is a prospective, multicentre web-based registry (www.trials-network.org). PsA patients who had at least 1 year of disease duration were included for this analysis. Patients were considered in MDA when they met at least 5/7 of the MDA criteria (figure 1). Results: In January 2018, 1283 patients from Turkey and 119 patients from Canada were recruited, 317 of whom had full data for MDA and were included in this analysis. The demographics, disease characteristics and patterns in patients with MDA achieved vs not are summarised in the table. There were no differences regarding demographics in both groups. The monoarthritis subtype (RR: 2.01, 95% CI: 1.579–2.559), the absence of enthesitis (RR: 1.570, 95% CI: 1.027–2.398) and the absence of distal interphalangeal joint disease (RR: 1.1, 95% CI: 1.001–1.25) were associated with higher probability of achieving MDA. Across different domains included in MDA, pain VAS≤15 and PtGA ≤20 could less frequently be achieved even when MDA is fulfilled as 44.5% and 26.5% of patients respectively still did not fulfil these domains (figure 1). On the other hand, for patients that did not achieve MDA, the body surface area (51.2%) and swollen joint count (53.5%) domains could be achieved in the majority of the patients and 93.5% of them had no enthesitis using the Leeds enthesitis index. Physician global assessment (>21 vs≤20) and BASDAI (>41 vs≤40, only for axial disease) had only moderate agreement with MDA (achieved or not) (kappa=0.47, p=0.05 and kappa=0.469, p=0.072; respectively). All data were given n/total n (percentage (%)) or median (first-third percentiles)*. MDA: minimal disease activity; PsA: Psoriatic Arthritis; DIP: distal interphalangeal. Conclusions: The MDA criteria provide an objective target for treatment in trials and clinical practice; however in real life PROs are the most significant barriers to achieve MDA within all domains. Leeds enthesitis index was not able differentiate MDA, for being negative in the vast majority of the patients. Monoarthritis subtype is a good prognostic factor whereas DIP joint disease and history of enthesitis are poor prognostic factors to achieve MDA. Disclosure of Interest: None declared